Handbook of surgery - Jain, Sudhir Kumar; Manchanda, Vivek; Tanwar, Raman (CBS Publishers & Distributors, 2014)
It is a compilation of lectures of general surgery delivered by an eminent teacher and his notes taken by two of his students. These notes have been selected according to the needs of the students and thoroughly revised and updated. There are many topics which have been simplified and would immensely benefit the postgraduate students who are in the process of learning the art and craft of surgery. This book is a perfect companion to the standard surgical text as it focuses on the topics relevant from the practical and theoretical points of view apart from acting as a handy source of information